Model Development of Household Well-Being of Resource-Based Coastal Fishing Coastal Maritime In The Riau Islands Province - Hamta, Firdaus; ., Ujianto; Sardjono, Sigit (Archives of Business Research, 2018)
This research is the development model of household welfare coastal fishing in the Riau Islands province in utilizing the potential of the maritime resources in the coastal province of Riau Islands. The population of the research was the fishing households in the coastal province of Riau Islands as much as 398 samples. Testing research of generalization done by using Least Square Estimation (GLS) model, the analysis of Structural Equation Models (SEM) with proportionate sampling method and use AIDS AMOS 21 consisting of: 5 variables, 21 63 indicators and instruments. Test results showed the model fit the resulting value of the chi square 183.813, significance probability 0057, GFI, AGFI 0.956 0.934, TLI 0.940, CFI 0.956, RMSEA 0.022, CMIN/DF 1.186 are all in the range of expected value so that the model can be accepted. The results showed that: (1) maritime coastal resource potential significant effect against the policy of the local government; (2) maritime coastal resource potential influential significantly to community empowerment; (3) the potential resources of the coastal maritime effect is not significantly to household economic behavior of coastal fishing; (4) community empowerment not significant effect against the economic behaviour of households coastal fishing; (5) the policy of local government economic behavior significantly to the influential households coastal fishing; (6) household economic behavior of coastal fishing effect significantly to public welfare_RTNP; (7) the local government policy take effect is not significantly to public welfare_RTNP; (8) community empowerment effect is not significantly to public welfare_RTNP; (9) maritime coastal resource potential effect is not significantly to public welfare_RTNP. Based on those results showed that the potential resources of the coastal maritime province Kepri can support the household well-being of fishermen on the coast, but has not yet been optimally utilized and not to increase well-being. Model development of household well-being coastal fishing can be used as an alternative in utilizing and managing maritime resource potential in the coastal province of Riau Islands province by improving several indicators to support relationship variable. The name of model of the development of household well-being coastal fishing is called ERDOGANA based management resource potential and utilization of maritime coast.